Everett Sanders papers - Sanders, Everett, 1882-1950
Correspondence, speeches, writings, press releases, and printed matter. Includes eleven volumes of reading copies of President Calvin Coolidge's speeches relating chiefly to Republican Party policies and to the presidential campaign of 1932. Correspondents include Calvin Coolidge, Herbert Hoover, Charles Evans Hughes, Theodore Roosevelt, and William H. Taft.
Lawyer, U.S. representative from Indiana, secretary to President Coolidge, and Republican Party national chairman.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Coolidge, Calvin, -- 1872-1933.; Coolidge, Calvin, -- 1872-1933 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Hughes, Charles Evans, -- 1862-1948 -- Correspondence; Roosevelt, Theodore, -- 1887-1944 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Republican Party (U.S. : 1854- ); Elections -- United States -- 1932.; Presidents -- United States -- Election -- 1932.; United States -- Politics and government -- 1901-1953.; Lawyers; Politicians; Representatives, U.S. Congress -- Indiana; Secretaries, Presidential